HIDROLISIS LIGNOSELULOSA PELEPAH DAN TANDAN KOSONG KELAPA SAWIT DENGAN KATALIS ZIRKONIA TERSULFATASI - Anis Kristiani; Kiky Corneliasari Sembiring; Haznan Abimanyu; Fauzan Aulia (Research Center for Chemistry - LIPI, 2013)
Lignocellulosic biomass which are frond and empty fruit bunches (EFB) is second generation raw material for ethanol production. Lignocellulose usage is expected to create a green process. Utilization of lignocellulose materials into ethanol involved four main processes, i.e pretreatment, hydrolysis/sacharification, fermentation, distillation and dehydration ethanol that was product. This research aims to optimize hydrolysis process of EFB and frond by using sulfated zirconia catalyst characterized its physical and chemical properties as a solid acid catalyst. Catalytic hydrolysis process conducted at 160 DCfor 3 hours gave the highest TRS (Total Reducing Sugar) which is 17,51 % for EFB while for frondfor 2 hours which is 19,23 % .Keyword: Hydrolysis, solid acid catalyst, lignocellulose, frond, EFB, sulfated zirconia